FINANCIAL PERFORMANCE ANALYSIS USING LIQUIDITY RATIO, SOLVENCY RATIO AND RENTABILITY RATIO IN KOPERASI WANITA KOTO KOCIAK SUB-DISTRICT IN GUGUAK LIMA PULUH KOTA DISTRICTS - Suci Permata Hati; Mariaty Ibrahim (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
The purpose of this research is to know the financial performance of Koperasi Wanita (KOPWAN) Koto Kociak sub-district in Guguak districts in Lima Puluh Kota from 2013 to 2017 using analysis of liquidity , solvency and rentability rations. The research method employed in secondary data which data from the financial statements. The data collection techniques that used are observation and documentation method. The data analysis techniques that used are by calculating liquidity, solvency and rentability rations. Based on the financial data analysis of Koperasi Wanita (KOPWAN) Koto Kociak sub-district in Guguak in Lima Puluh Kota districts the researcher found that the liquidity rate from 2013 up to 2017 as indicated by the current ratio very good results, quick ratio very good results and cash ratio gets poor results. The solvency rate from 2013 up to 2017 as indicated by DAR and DER shows good results. The rentability rate from 2013 up to 2017 as indicated by ROA and ROE shows good results. According from the calculating analysis by liquidity, solvency and rentability rations, it said the financial performance of Koperasi Wanita (KOPWAN) Koto Kociak sub-district in Guguak districts in Lima Puluh Kota needs to be improved again. Keywords : Financial Performance, Liquidity Ratio, Solvency Ratio and Rentability Ratio